Case Study of the Application of Digital Marketing in Increasing the Competitiveness of MSMEs in the Industrial Era 4.0 - Frilla Gunariah; Neli Purwanti; Amelia Amelia (Politeknik Siber Cerdika Internasional, 2025)
This study aims to analyze the application of digital marketing in increasing the competitiveness of MSMEs in Indonesia, focusing on three MSME actors in various sectors: culinary, handicrafts, and retail. Through in-depth interviews, it was found that digital marketing has a positive impact on product visibility, market reach, and interaction with customers. Social media platforms such as Instagram, Facebook, and marketplaces such as Shopee and Tokopedia allow MSMEs to reach a wider range of consumers, reduce marketing costs, and increase sales. However, the challenges faced by MSMEs include price competition in the marketplace, limited human resources in digital marketing management, and consistency in content creation. This study concludes that the success of the implementation of digital marketing is highly dependent on internal readiness, technology access, and planned strategies. Therefore, MSME actors need to strengthen their digital capabilities through more efficient training and resource management to maximize the potential of digital marketing and strengthen competitiveness in an increasingly competitive global market. The research provides practical implications for MSME practitioners in formulating adaptive digital strategies, for policymakers in designing targeted digital literacy programs, and for business incubators in developing sector-specific mentoring frameworks to enhance the digital competitiveness of Indonesian MSMEs.